Enhancing the Capacity of Healthcare Cadres in Data Management: A Simulation-Based Approach to Strengthen Healthcare Systems - Rahma Cahyani, Aulia; Tri Gustiani Nur Athaya, Aulia; Hasnarini Putri, Nadya; dwi Tafia, Sabrina; Vernicia Humairo, Mika (Inovasi Lokal, 2025)
The increasing demand for efficient data management in healthcare has highlighted the need to enhance the capacity of healthcare cadres in handling health-related information. This study evaluates the effectiveness of a role-playing simulation in improving data management skills among healthcare workers. The simulation involved 10 groups, each comprising 4-5 participants, who were assigned unique patient referral scenarios requiring collaboration and problem-solving. Results demonstrated a 40% reduction in data entry errors and improved proficiency in navigating electronic health record systems, with 85% of participants successfully generating basic reports post-training. Reflection sessions revealed persistent systemic challenges, such as limited resources and communication gaps, while also emphasizing the value of teamwork and continuous professional development. The findings align with existing literature on experiential learning and competency-based education, which stress the importance of hands-on training and real-world application. By addressing both technical and systemic barriers, this approach not only enhances individual competencies but also strengthens healthcare delivery systems. These insights underscore the critical role of tailored capacity-building programs in empowering healthcare cadres and achieving sustainable improvements in health data management.